The Effect Of Additive Covid19 Positive Cases And World Gold Prices On The Joint Share Price Index In Indonesia Stock Exchange Period July 2020 - December 2020 - Vivin Hanitha; Marselia Purnama; Octavianti Purnama (Fakultas Bisnis, 2021)
This research was conducted on the price of the Composite Stock Price Index in the Indonesia Stock Exchange. In this study using a purposive sample method as a sampling method. The samples used were world gold prices, additional positive cases of Covid19, and IHSG from July 2020 to December 2020 so that 121 observational data were obtained. In testing the hypothesis in this study, it was carried out in five ways, namely the classical assumption test, multiple linear regression analysis, partial test (t test), simultaneous test (f test), and the coefficient of determination test. From the results of the eviews test, it was found that the addition of positive cases of covid19 and world gold prices affected the JCI both partially and simultaneously with an R square value of 0.416189 or 41.6189%.